Pengembangan Lembar Kerja Siswa (LKS) Berbasis Karakter melalui Pendekatan Saintifik pada Materi Fluida Statik untuk Sekolah Menengah Atas - Husna Mayasari; Syamsurizal Syamsurizal; Maison Maison (Universitas Jambi, 2015)
The purpose of this study is to create students’ worksheet based on characters through scientific approach of statistical fluid material, to examine the feasibility of worksheet according for experts, teachers and students, to investigate the effectiveness of the development of students' character and skills of the students in doing practical work after using worksheet. This research uses design R & D with model Dick and Carey. The research procedure includes four stages, which is analizing, designing, creating, and evaluating stage. The feasibility of worksheet was examined using a questionaire. Based on the result questionaire validity tested by the experts, the worksheet was declared to be valid and it is apliable to be used and tested,, whereas the response of the teachers and students about the worksheet, it stated that the worksheet categorized as a very good one. Meanwhile the data of character development and students skill on doing practical work that gained from the observation sheet. Analysis of the character development shows that the character of the students are in the category began to evolve become as a habit (culture of the students), while the influence of worksheet to the students’ skill on doing practical are in good criteria.